Preparation and pH‐Dependent Properties of Hydrogels Based on Acidic Copolymers with PEG Side Chains and α‐Cyclodextrin. Issue 12 (9th May 2019) - Stößlein, Sebastian; Grunwald, Ingo; Khachikyan, Alexander; Faßbender, Fabian; Thiel, Karsten; Hartwig, Andreas
Abstract: A variety of differently structured PEG‐based polymers can form physically cross‐linked PEG hydrogels with α‐cyclodextrin. The polymer structures strongly influence the properties of the hydrogel and its formation. Four different copolymers of methoxy PEG methacrylate and methacrylic acid are used together with α‐cyclodextrin to study hydrogel formation speed and gel strength. The hydrogels are formed within 1–25 min, and the formation process is examined in situ by dynamic light scattering. The gel formation time is pH dependent due to the methacrylic acid present in the polymers. The gel strength examined by texture analyzer also depends on the composition and pH. With prior mechanical destruction, all hydrogels are dissolvable in an excess of water, being a useful feature for an in vivo usage. By analyzing the structures of the hydrogels with confocal light microscopy (laser scanning confocal microscopy) and scanning electron microscope (SEM) after freeze etching, the different hydrogel structures can be observed. Abstract : Hydrogels made from copolymers of methoxy PEG methacrylate and methacrylic acid (MA) (mPEGMA‐co‐MA) physically cross‐linked with α‐cyclodextrin are examined in terms of formation speed, melting point, mechanical stability, and structure. The data indicate that the incorporation of non‐gelation monomers like MA has a beneficial effect on the structure and stability of the hydrogel.